Effects of Eugenia umbelliflora O. Berg (Myrtaceae)-leaf extract on inflammation and hypersensitivity. (15th November 2019) - Goldoni, Fernanda Capitânio; Barretta, Claiza; Nunes, Roberta; Broering, Milena Fronza; De Faveri, Renata; Molleri, Heloisa Tachini; Corrêa, Thiago Patrício; Farias, Ingrid Vicente; Amorin, Clarissa Krieger; Pastor, Maria Veronica Davila; Meyre-Silva, Christiane; Bresolin, Tania Mari Belle; et al.
Abstract: Ethnopharmacological relevance: The leaves of Eugenia species are widely used in popular medicine to treat several diseases, such as arthritis, rheumatism and diabetes. Eugenia umbelliflora O. Berg is popularly known in Brazil as "baguaçu", name also conferred to Eugenia jambolana probably due to their apparent similarity. Although the popular use scientifically proved of E. jambolana as anti-diabetes and also as anti-inflammatory, there are only two scientific studies demonstrating anti-ulcer and bactericide activities of E. umbelliflora leaves extract, without reference to its possible anti-inflammatory activity. Aim of the study: The aim of this study was to show the anti-oxidant and anti-inflammatory activity of the methanol extract obtained from E. umbelliflora leaves (EuL) using in vitro and in vivo protocols. Materials and methods: The total phenolic content was evaluated using the folin-Ciocalteu colorimetric method and phloroglucinols content by HPLC. The anti-oxidant activity was evaluated by ORAC, ABTS +, DPPH, and metal chelation methods. The anti-inflammatory activity was investigated using carrageenan-induced inflammation in the subcutaneous tissue of male Swiss mice orally pre-treated with the EuL (0.3, 1 or 3 mg/kg). The leukocyte influx (optical microscopy) and secretion of chemical mediators (TNF, IL-6, IL-1β and CXCL1, by enzyme-linked immunosorbent assay) were quantified in the inflamed exudate. Histological analysis of the pouches was also performed. The anti-hypersensitive activity was investigated using carrageenan-induced mechanical hypersensitivity and mice were then evaluated using the von Frey filaments. The Open Field test was used to evaluate possible interference of adverse effect of EuL on locomotor activity that could lead to misinterpretation of the hypersensitivity evaluation. Results: The EuL demonstrated important and moderate reducing capacity on ABTS + and DPPH assays, respectively, but with slight activity in ORAC test. It reflects low protection against cell damage. The EuL also presented 30% of phenolic compounds. The phloroglucinols content of EuL was 25.9 mg/g, 18.4 mg/g and 16.6 mg/g of eugenial C, eugenial D and eugenial E, respectively. The in vivo analysis of the inflammatory exudate of EuL-treated mice demonstrated reduction in the polymorphonuclear cells (PMN) migration to the inflamed tissue, as well as the reduction of the pro-inflammatory cytokine IL-1β. Histologically, it was observed evident decrease in the oedema, formed essentially by non-haemorrhagic fibrin exudate, as well as PMN infiltrate, when compared with control mice injected with carrageenan. Furthermore, the extract also presented effective reduction of the mechanical hypersensitivity induced by carrageenan without any interference in animal's locomotor and exploratory activity. Conclusions: Together, the results herein obtained show that EuL presented anti-inflammatory activity by decreasing the influx of PMN to the inflamed tissue, as well as the cytokine IL-1β level. This anti-inflammatory activity was also accompanied by significant anti-hypersensitive effect. The effects presented by EuL seem not to be correlated with an antioxidant activity. However other extract chemical compounds could be responsible for its important anti-inflammatory effects. Graphical abstract: Image 1